A modified Fermi-Walker derivative for inextensible flows of binormal spherical image - Suroglu, Gulden Altay (De Gruyter Poland Sp Z O O, 2018)
Fermi-Walker derivative and biharmonic particle play an important role in skillful applications. We obtain a new characterization on binormal spherical indicatrix by using the Fermi-Walker derivative and parallelism in space. We suggest that an inextensible flow is the necessary and sufficient condition for this particle. Finally, we give some characterizations for a non-rotating frame of this binormal spherical indicatrix.
Keywords: Fermi-Walker derivative-parallelism; Energy; Bienergy; Heisenberg group; Faraday tensor